Negative group delay of reflected Weyl quasiparticles - Mou Yang; Hai-Yan Li; Rui-Qiang Wang (New Journal of Physics, 2021)
When an electron is incident from a Weyl material to an insulator and totally reflected, it suffers a reflection group delay and a reflection shift (Goos–Hänchen and/or Imbert–Fedorov shifts). We found the group delay is negative for half of the incident states. The negative group delay does not mean the electron is bounced back before its injection, but is an effective acceleration of the electron near the interface induced by self-interference. The reflection shift orients circulating the points at which the surface-bulk state transition occurs. The reflection shift and the group delay cause velocity correction of the bound states in the Weyl material sandwiched by two insulators. The velocity correction features induced by the negative group delay were verified by a tight-binding calculation, in which the concept of group delay is not used.